ARCHITECTURE OF THE UNIVERSITY VIRTUAL WAREHOUSES SYSTEM OF "OPENED ACCESS" - V. Timofeev; Y. Timoshin; V. Yarchenko; T. Shemsedinov (Kherson State University, 2010)
The article describes system developed for Virtual Warehouses with the opened access support in the environment of the corporate applied network for NTUU «KPI». Such system may use as a component in scope of Ukraine electronic goverment system. System is the part of the pilot standard developed for computer-integrated access center for University informative resources processing and archiving, including the use of national education GRID components. The architecture is developed for realization at corporate level taking into account computer security and management requirements.